Model checking agent of SMS management system for direct sales and network marketing - Abdul Bujang, Siti Dianah; Selamat, Ali (2008)
The revolution and globalization towards the use of technology in Short Messaging Services (SMS) has leaded many electronic businesses in our country. As introduced, the SMS Management System in Direct Sales and Network Marketing is one of the integrated information systems which implemented the SMS technology for greater performance. The enhancement of connection and communication among cluster of distributors has contributed higher level of the business networking system.However, several uncertainties issues that occurred during system implementation have not yet proving the trustworthiness of system validity. Therefore, this problems lead to such an impact in terms of costing for maintenance and to control the quality of the system.This paper presents the issues by proposing the design of model checking agent to verify and validate the system model based on the specification required. This approach investigates how software agent is able to play a role in handling each of the state transition.We use model checker SPIN to SMS Management System agent model for failure detection.This approach is to confirm the system is reliable, robust and secure in controlling the data protocol.